A comprehensive evaluation of apixaban in the treatment of venous thromboembolism. Issue 2 (1st February 2020) - Koehl, Jennifer L; Hayes, Bryan D.; Al‐Samkari, Hanny; Rosovsky, Rachel
ABSTRACT: Introduction : The emergence of the direct oral anticoagulants (DOACs) offers patients more convenient and accessible alternatives to warfarin or parenteral agents for the treatment of venous thromboembolism (VTE). Apixaban (Eliquis®) is an oral, direct factor Xa inhibitor that is approved for the acute treatment of deep-vein thrombosis (DVT) and pulmonary embolism (PE) as well as for the reduction in the risk of recurrent DVT and PE following initial therapy. Areas covered : This article reviews results from preclinical and healthy volunteer studies, large phase III trials evaluating the safety and efficacy of apixaban, as well as key studies that led to apixaban's current licensing. This review also will provide an overview of special populations where future areas of research are needed. Expert commentary : Apixaban offers several advantages over historical therapy for the treatment and secondary prevention of VTE. However, there are some populations in which the use of apixaban has not been extensively studied such as patients >75 years old, or those with cancer, low or high body weight, or poor renal function. Likewise, there is a dearth of data on pediatric patients and patients with a history of heparin-induced thrombocytopenia or identified forms of thrombophilia. Additional comparator studies on anticoagulation reversal involving andexanet alfa are also necessary to further assess its hemostatic efficacy and prothrombotic risk.